ACE gene polymorphism and severe lung injury in patients with COVID-19 (2020)
COVID-19 has markedly varied clinical presentations, with the majority of patients being asymptomatic or having mild symptoms. However, severe acute respiratory disease caused by SARS-CoV-2 is common and associated with mortality in patients who require hospitalization. The etiology of susceptibility to severe lung injury remains unclear. Angiotensin II, converted by angiotensin-converting enzyme (ACE) from angiotensin I and metabolized by angiotensin converting enzyme 2 (ACE2), plays a pivotal role in the pathogenesis of lung injury. ACE2 is identified as an essential receptor for SARS-COV-2 to enter the cell. The binding of ACE2 and SARS-COV-2 leads to the exhaustion of ACE2 and down-regulation of ACE2. The interaction and imbalance between ACE and ACE2 result in an unopposed angiotensin II. Considering that the ACE insertion/deletion (I/D) gene polymorphism contributes to the ACE level variability in general population, in which mean ACE level in DD carriers are approximately twice that in II carriers, we propose a hypothesis of genetic predisposition to severe lung injury in patients with COVID-19. It is plausible that the ACE inhibitors and ACE receptor blockers (ARBs) may have the potential to prevent and to treat the acute lung injury after SARS-COV-2 infection especially for those with the ACE genotype associated with high ACE level.